Human Resources Competences in Economics Higher Education Provider in East Java, Indonesia : The determinant of organizational performances - Fariz, Fariz (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
This study seeks to fill a gap (gap) is to integrate human resource competencies, and a culture of innovation in improving organizational performance and competitiveness, especially in the Economics Higher Education Institutes (STIE) in East Java.The study population was the whole STIE in East Java as it listed in LLDIKTI who has at least 50% of study program accredited